ZFP57 regulates DNA methylation of imprinted genes to facilitate embryonic development of somatic cell nuclear transfer embryos in Holstein cows - Tong Yu; Ru Meng; Weijia Song; Hongzheng Sun; Quanli An; Chengtu Zhang; Yong Zhang; Jianmin Su (Journal of Dairy Science, 2023)
ABSTRACT: Aberrant epigenetic nuclear reprogramming, especially imprinting pattern disorders, is one of the major causes of failure of clone development from somatic cell nuclear transfer (SCNT). Previous studies showed that ZFP57 is a key protein required for imprint maintenance after fertilization. In this study, we found that imprinting control regions in several imprinted genes were significantly hypomethylated in cloned embryos compared with in vitro fertilization embryos, indicating a loss of imprinted gene methylation. The ZFP57 expression was capable of maintaining the correct degree of methylation at several imprinting control regions and correcting abnormal hypomethylation. Moreover, we successfully obtained bovine fetal fibroblasts overexpressing ZFP57, which were used as donors for SCNT. Our results demonstrated that overexpression of ZFP57 increased total and trophectoderm cell numbers and the ratio of inner cell mass to total cells, reduced the apoptosis rate and significantly enhanced the development of SCNT blastocysts in vitro, ultimately achieving a degree of methylation similar to that in in vitro fertilization embryos. We concluded that overexpression of ZFP57 in donor cells provided an effective method for enhancing nuclear reprogramming and developmental potential in SCNT embryos. The ZFP57 protein played a key role in maintaining the methylation of imprinted genes during early embryonic development, which may be effective for enhanced SCNT in cattle.